Pengelolaan Surat dan Berkas Masuk di BKD: Peran Strategis Layanan Informasi - Isnani Nazwatunissa; Nurul Hikmah (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
This article examines the management of incoming letters and files at the Regional Civil Service Agency (BKD) of Central Kalimantan Province, focusing on the strategic role of information services as instruments of transparency and bureaucratic reform. Using a descriptive qualitative approach, the research was conducted through in-depth interviews with five employees and participatory observation during an internship, revealing a systematic workflow: receipt, recording, disposition by the Agency Secretary, distribution to relevant fields, and filing. The results show the effectiveness of this mechanism in handling 20-30 documents daily, despite challenges such as dependence on physical archives, risk of data loss, and limitations in digitization that could potentially cause delays. Key recommendations include training in file digitization, developing integrated SOPs, action research simulations, and an internal database platform to increase efficiency by up to 50% and strengthen public access to information. The conclusion emphasizes that incoming mail management is not merely a routine task, but a strategic foundation for accountable ASN governance, with a recommendation for further research to integrate information technology to overcome structural obstacles.